Hydrogelled emulsion from chia and linseed oils: A promising strategy to produce low-fat burgers with a healthier lipid profile - Heck R.T. (2019)
This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – Brasil (CAPES) – Finance Code 001 and by the Conselho Nacional de Desenvolvimento Científico e Tecnológico – CNPq [grant number 425577/2018-0]. E. Saldaña received the support from the “Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica – CONCYTEC” from Peru (CIENCIACTIVA programme, PhD scholarship contract agreement No. 104-2016-FONDECYT). P.C.·B Campagnol and J.M. Lorenzo are members of the HealthyMeat network, funded by CYTED (ref. 119RT0568).